Mindful Virtue, Mindful Reverence - Goodenough, Ursula (Zygon, 2001)
How does one talk about moral thought and moral action as a religious naturalist? We explore this question by considering two human capacities: the capacity for mindfulness, and the capacity for virtue. We suggest that mindfulness is deeply enhanced by an understanding of the scientific worldview and that the four cardinal virtues—courage, fairmindedness, humaneness, and reverence—are rendered coherent by mindful reflection. We focus on the concept of mindful reverence and propose that the mindful reverence elicited by the evolutionary narrative is at the heart of religious naturalism. Religious education, we suggest, entails the cultivation of mindful virtue, in ourselves and in our children.